Letter: faecal microbiota transplantation for IBS - Segal,JP; Mullish,BH; Quraishi,MN; Iqbal,TH (Alimentary Pharmacology & Therapeutics, 2020)
LINKED CONTENT This article is linked to Lahtinen et al papers. To view these articles, visit https://doi.org/10.1111/apt.15810 and https://doi.org/10.1111/apt.15875 .